Molecular characterization of methicillin-resistant Staphylococcus aureus among insulin-dependent diabetic individuals in Brazil - Teixeira, Nathalia Bibiana [UNESP]; Castelo Branco Fortaleza, Carlos Magno [UNESP]; de Souza, Matheus Cristovam [UNESP]; Monteiro Pereira, Thais Aline [UNESP]; de Camargo Colenci, Bibiana Prada [UNESP]; Ribeiro de Souza da Cunha, Maria de Lourdes [UNESP] (Springer Nature, 2021)
Background: People with diabetes mellitus, especially insulin-dependent diabetic patients, are a risk group for staphylococcal infections. Asymptomatic infection with Staphylococcus aureus is common and favors dissemination of the microorganism, rendering these individuals a source of infection. This study aimed to characterize the resistance profile, clonal profile and sequence type, as well as to analyze the prevalence and risk factors for nasal and oropharyngeal carriage of methicillin-susceptible (MSSA) and methicillin-resistant S. aureus (MRSA) isolated from insulin-dependent diabetic individuals in the city of Botucatu, SP, Brazil. Methods: Staphylococcus aureus was collected from the nasopharynx and oropharynx of 312 community-dwelling insulin-dependent diabetic individuals over a period of 3 years (October 2015 to December 2018). The isolates were characterized by susceptibility profiling, detection of the mecA gene, SCCmec typing, and molecular typing by PFGE and MLST. The risk factors associated with S. aureus and MRSA carriage were determined by logistic regression analysis. Results: The overall prevalence of colonization with S. aureus and MRSA was 30.4% and 4.8%, respectively. Fifteen of the 112 S. aureus isolates carried the mecA gene; SCCmec type IV was identified in 10 isolates, SCCmec type I in three, and SCCmec type II in two. Among the 15 resistant isolates (MRSA), four were susceptible to oxacillin/cefoxitin by the disc diffusion method and one MSSA isolate was resistant to sulfamethoxazole/trimethoprim. The analysis of risk factors revealed a protective effect of age and lung disease, while lower-extremity ulcers were a risk factor for S. aureus. For MRSA, only male gender was significantly associated as a risk factor in multivariate analysis. Clonal profile analysis demonstrated the formation of clusters among MRSA isolates from different patients, with the identification of ST5-IV, ST5-I, and ST8-IV. Isolates carrying ST398 were identified among MSSA and MRSA (ST398-IV). Conclusion: Our findings reinforce the importance of epidemiological studies of S. aureus carriage, especially in populations at high risk of infections such as diabetics. The data suggest widespread dissemination of MRSA in the population of insulin-dependent diabetic patients studied, as well as the emergence of important lineages among these individuals.
Keywords: Diabetes mellitus; Insulin; Methicillin-resistant Staphylococcus aureus (MRSA); Molecular typing; Nasal or oropharyngeal carriage; Resistance